Büntetőexpedíció - Magyar, Dezső (Hungary : Balázs Béla Stúdió, 1970)
In 1913, the cavalry unit of the Monarchy leads a retaliatory action against a Serbian village, where an Austrian officer was killed. The film examines the chances of rebellion against the steadfastness of power.
Keywords: Documentary films